2021
DOI: 10.1101/2021.04.30.21256373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitude and Perceived Barriers towards Research among Undergraduate Medical Students of Bangladesh

Abstract: Background: Undergraduate research opportunities teach students not only how to conduct research, but they too learn problem-solving aptitudes. Participating in research also increases students' interest is being involved and making special contributions to the academic field. Therefore, the aim of our study was intended to assess the attitude and perceived barriers toward research among the medical undergraduates of Bangladesh. Methods: A cross-sectional questionnaire survey was conducted among third, fourth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Introducing the medical student to the fundamentals of medical research at initial phases improve their skills in searching, analyzing and evaluating medical journals, self-directed learning, and drafting [28,29] In comparison to individuals who did not get training, physicians who got undergraduate research training had a more favorable attitude toward research and faced fewer hurdles [26]. Despite the fact that undergraduate medical students are passionate about performing medical research, they are unable to develop the ability to conduct research due to a number of difficulties, insufficient incorporation of research methodology in the undergraduate curriculum [30]. According to a survey, the most significant research challenges were insufficient research time (76.5%), insufficient financial assistance (63%), and a lack of financial incentives (51%) [31].…”
Section: Resultmentioning
confidence: 99%
“…Introducing the medical student to the fundamentals of medical research at initial phases improve their skills in searching, analyzing and evaluating medical journals, self-directed learning, and drafting [28,29] In comparison to individuals who did not get training, physicians who got undergraduate research training had a more favorable attitude toward research and faced fewer hurdles [26]. Despite the fact that undergraduate medical students are passionate about performing medical research, they are unable to develop the ability to conduct research due to a number of difficulties, insufficient incorporation of research methodology in the undergraduate curriculum [30]. According to a survey, the most significant research challenges were insufficient research time (76.5%), insufficient financial assistance (63%), and a lack of financial incentives (51%) [31].…”
Section: Resultmentioning
confidence: 99%
“…These challenges have been consistently reported in other studies. 7 , 9 , 11 , 15 However, Al Kuwaiti and Subbarayalu's study listed the most commonly reported barriers as lack of institutional motivation, lack of infrastructural activities, and lack of faculty involvement. 21 Others reported inadequate internet connection, language barriers, and insufficient financial support as the main challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Similar motivators have been found in other studies. 4 , 7 , 11 For instance, a recent study carried out in medical schools in Uganda showed that for certain students, passion for research serves as the main driver of research engagement. 12 Furthermore, Kiyimba et al 12 revealed that guidance on manuscript writing and publication can serve as a motivator for many students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Assar A et al (2022) [ 15 ] Six Arab Countries (Egypt, Algeria, Sudan, Jordan, Syria and Palestine) The top ten perceived barriers towards research practice in the entire sample were lack of access to lab equipment for research, priority of education over research, lack of time because of educational tasks, generally poor attention given to researchers, lack of fund, poor collaboration between different academic departments and research centers, Insufficient research skills, lack of suitable research space, lack of faculty input and lack of familiarity with research studies. Ferdoush J et al (2022) [ 16 ] Bangladesh Majority of the respondents reported that inadequate time and priorities, insufficient guidance, inadequate familiarities with research methodology and statistical analysis were the barriers of research. Mugabo E et al (2021) [ 17 ] Rwanda The most significant barrier to research participation was students' belief that they lacked knowledge of research processes.…”
Section: Barriers and Challenges Facing Involvement Of Undergraduate ...mentioning
confidence: 99%